Improvement Grade 4 Science Learning Outcomes with Video Assisted Problem Based Learning Model - Eva Fitri Hidayanti (Universitas Sebelas Maret, 2020)
This article describes the improvement of students' science learning outcomes by applying a video-assisted problem-based learning model in class IV SD Negeri Watujaran in the 2020/2021 learning year. This study uses three cycles. Where each cycle begins with planning, implementing, observing, and reflecting. The results of this study were that in cycle 1 there was an increase from pre-cycle, 58% of students were complete and in cycle 2 there was an increase from cycle 1, 91,% of students were complete, and in cycle 3 the results of students learning completeness reached 100% of the 12 students. These results indicate that the application of the video-assisted problem-based learning model can improve the science learning outcomes of students at SD Negeri Watujaran.